Legal Protection of Depositors' Funds in The Event of Bank Liquidation - Anak Agung Ngurah Bagus Krisna Pratama; Johannes Ibrahim Kosasih; Ni Komang Arini Styawati (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2023)
In general, a bank is a financial intermediary institution generally established with the authority to accept money deposits, lend money, and issue promissory notes or what is known as banknotes, banks in carrying out one of their functions are collecting funds from the public in other words, storing funds in the bank gets the benefit of interest for customers, in this case not all the benefits promised by the bank can be realized the higher the interest it seems that we as customer consumers feel benefited, but in reality there are banks that provide high interest after that the health of their banks decreases so that it has an impact on customer consumers on their savings at the bank. The formulation of the problems raised in this study are 1). What are the consequences or legal consequences for banks in the placement of funds that are not in accordance with the LPS policy in the event that the bank is not healthy? 2). How is the legal protection of depositors in the event that the bank is liquidated by LPS? This research uses normative legal research methods, namely research by collecting and analyzing secondary data using secondary data sources only, namely books related to the problem, relevant laws and regulations, relevant court decisions, legal theories and relevant scholars' doctrine experts, and case studies related to legal issues, the theory used to analyze the theory of satisfaction, the theory of legal certainty and the theory of legal protection. The conclusion of this research is to provide protection to customers if they save funds in banks that are determined to be unhealthy by the Deposit Insurance Corporation so that customers feel safe if they want to save their funds in the banking world.